Optimal Control of Diffusions with Hard Terminal State Restrictions. (13th December 2012) - Seierstad, Atle
Abstract : A maximum principle is proved for certain problems of optimal control of diffusions where hard end constraints occur. The results apply to several dimensional problems, where some of the state equations involve Brownian motions, but not the equations corresponding to states being hard restricted at the terminal time.